Cross-Talk between Adiponectin and IGF-IR in Breast Cancer - Mauro, Loredana; Naimo, Giuseppina Daniela; Ricchio, Emilia; Panno, Maria Luisa; Andò, Sebastiano (Frontiers in Oncology, 2015)
Obesity is a chronic and multifactorial disorder that is reaching epidemic proportions. It is characterized by an enlarged mass of adipose tissue caused by a combination of size increase of preexisting adipocytes (hypertrophy) and de novo adipocyte differentiation (hyperplasia). Obesity is related to many metabolic disorders like hypertension, type 2 diabetes, metabolic syndrome, cardiovascular disease, and it is associated with an increased risk of cancer development in different tissues including breast. Adipose tissue is now regarded as not just a storage reservoir for excess energy, but rather as an endocrine organ, secreting a large number of bioactive molecules called adipokines. Among these, adiponectin represents the most abundant adipose tissue-excreted protein, which exhibits insulin-sensitizing, anti-inflammatory and antiatherogenic properties. The serum concentrations of adiponectin are inversely correlated with body mass index. Recently, low levels of plasma adiponectin have been associated with an increased risk for obesity-related cancers and development of more aggressive phenotype, concomitantly with alterations in the bioavailability of Insulin-like Growth Factor-I (IGF-I) and IGF-I Receptor (IGF-IR) signaling pathways. In this review we discuss the cross-talk between adiponectin/AdipoR1 and IGF-I/IGF-IR in breast cancer.